The Transnational Flow of Korean Pop Culture: A Case Study of Audience Reception in Romania - Alexandra Bija (Linguaculture)
This paper investigates the transnational flow of Korean pop culture in Romania, focusing on the reception and influence of K-pop, K-dramas, and Korean films among Romanian audiences. It examines how these cultural products are interpreted, adapted, and integrated into the local cultural landscape, highlighting the dynamic interplay between global trends and local contexts. Utilizing a mixed-methods approach, the study analyzes secondary sources and primary data gathered from a structured questionnaire distributed to fans. The findings reveal a significant increase in interest in Korean pop culture over the past decade, driven by high production values, engaging storytelling, and active fan communities. Additionally, the research identifies factors such as the role of social media, streaming platforms, and localized fan activities that contribute to the phenomenon’s popularity. Through the lens of cultural exchange theories, the study underscores the complexity of audience reception and the transformative nature of cultural products as they cross borders. Ultimately, this research contributes to a deeper understanding of transnational cultural flows and the impact of Korean pop culture on the evolving cultural dynamics in Romania.